2015
DOI: 10.1093/infdis/jiv111
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Glycoprotein Is Not Required for Ebola Virus Virulence in Guinea Pigs

Abstract: Ebola virus (EBOV) uses transcriptional editing to express several glycoproteins (GPs), including secreted soluble GP (sGP) and structural GP1,2, from a single gene. Recombinant viruses predominantly expressing GP1,2 are known to rapidly mutate and acquire an editing site predominantly expressing sGP in vivo, suggesting an important role of this protein during infection. Therefore, we generated a recombinant virus that is no longer able to express sGP and assessed its virulence in the EBOV guinea pig model. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…However, the fast emergence of revertants both in vivo and in vitro (in certain cell lines) when sGP production is reduced by introducing an 8A genotype (i.e. 8 uridine residues in the virus genome, leading to production of predominantly 8A mRNAs) in the editing site suggests an important role of sGP in the biology of ebolaviruses (Volchkova et al, 2011;Kugelman et al, 2012;Hoenen et al, 2015;Tsuda et al, 2015). In vitro, sGP exerts vascular effects, notably the restoration of the barrier function suggesting an anti-inflammatory role (Wahl-Jensen et al, 2005); however, the relevance of this finding is currently not clear.…”
Section: Gp: One Gene Many Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fast emergence of revertants both in vivo and in vitro (in certain cell lines) when sGP production is reduced by introducing an 8A genotype (i.e. 8 uridine residues in the virus genome, leading to production of predominantly 8A mRNAs) in the editing site suggests an important role of sGP in the biology of ebolaviruses (Volchkova et al, 2011;Kugelman et al, 2012;Hoenen et al, 2015;Tsuda et al, 2015). In vitro, sGP exerts vascular effects, notably the restoration of the barrier function suggesting an anti-inflammatory role (Wahl-Jensen et al, 2005); however, the relevance of this finding is currently not clear.…”
Section: Gp: One Gene Many Proteinsmentioning
confidence: 99%
“…Interestingly, when EBOV is serially passaged in certain cell lines like Vero cells, the GP gene gets modified to predominantly generate GP 1,2 by addition of an 8th U in the editing site (n.b., in contrast to transcriptional editing this occurs on the genome level) (Volchkova et al, 2011). However, when this EBOV is further passaged in animals or in other cell lines like Huh7 cells, the genotype reverts back so that sGP is again produced as the main product of transcription (Volchkova et al, 2011;Hoenen et al, 2015;Tsuda et al, 2015). This observation suggests that either the importance of the function of sGP or the importance of GP gene modulation is dependent on the host cell environment.…”
Section: Modulation Of Cytotoxicity and Inflammationmentioning
confidence: 99%
“…GP, the only transmembrane surface protein, is responsible for host cell binding and virus internalization 1 6 . Little is known about the functional roles of the secreted proteins sGP and ssGP 1 3 4 7 .…”
mentioning
confidence: 99%
“…Gross pathology and histology also revealed no departure from typical EVD historically reported in the literature [ 53 ]. Guinea pig studies with clones engineered to express either 7U or 8U have confirmed that either challenge results in fatal EVD with the 8U rapidly reverting to 7U [ 51 , 54 ]. Given the lack of differences between the end stage disease and the rapid return back to a predominantly 7U genotype, the data presented herein support the conclusion that an 8U challenge is attenuated compared to a 7U challenge, but only in the disease course and not in terms of lethality, especially considering that all animals had reverted back to the 7U majority population by the time of euthanasia.…”
Section: Discussionmentioning
confidence: 99%